Diabetic foot screening: why is it neglected? - Abu‐Qamar, Ma’en Zaid (Int Wound J, 2006)
Understanding reasons for the neglect of foot screening during the annual review of people with diabetes enables the development of solutions for this omission. This study explores the reasons within the context of health care delivery systems in terms of the professional, social, political and economic aspects of this screening. Information was obtained through reviewing publications on diabetic foot and health care reform. The omission of annual foot examination for people with diabetes is attributed to the nature of diabetes‐related foot problems, people with diabetes, health care professionals and the current structure of health care delivery systems. Increasing the adherence to foot screening for those with diabetes requires short‐ and long‐term strategies. Short‐ and long‐term strategies for reminding patients and staff about foot screening are suggested.